2017
DOI: 10.2214/ajr.16.17766
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 18F-FDG PET Metabolic Parameters Derived Using Simultaneous PET/MRI and Correlation With Prognostic Factors of Invasive Ductal Carcinoma: A Feasibility Study

Abstract: Semiquantitative FDG parameters derived with MRI-based attenuation correction in simultaneous PET/MRI are reliable and correlate with clinicopathologic features such as grade as well as subtype and thus could be used in the prognostication of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Such properties are reported to be different between BC subtypes which exhibit different biological aggressiveness and behavior [ 32 ]. TNBC is characterized by higher glucose metabolism, which is reflected in its higher SUV values compared with other BC subtypes as seen in other studies [ 32 , 33 ] as well as in this investigation. However, quantitative parameters (e.g., DWI-ADC values) alone do not seem to be accurate enough to discriminate molecular BC subtype; thus, more sophisticated AI-enhanced approaches are necessary [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…Such properties are reported to be different between BC subtypes which exhibit different biological aggressiveness and behavior [ 32 ]. TNBC is characterized by higher glucose metabolism, which is reflected in its higher SUV values compared with other BC subtypes as seen in other studies [ 32 , 33 ] as well as in this investigation. However, quantitative parameters (e.g., DWI-ADC values) alone do not seem to be accurate enough to discriminate molecular BC subtype; thus, more sophisticated AI-enhanced approaches are necessary [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…Duplicate articles, review articles, case reports, non-English publications, and articles, which not contain correlation coefficients between PET and Ki-67 were excluded (n= 1568). Therefore, the present analysis comprises 32 studies with 1801 patients ( Table 1 ) [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] . The following data were extracted from the literature: authors, year of publication, number of patients, histopathological parameters, and correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…This can be explained by the fact that TNBCs are often aggressive tumors whose pejorative histoprognostic factors (grade, proliferation rate, size, inflammatory tumor, lymph node involvement, etc.) are correlated with some metabolic parameters and pejorative features [24][25][26][27][28][29][30][31][32][33][34][35], whereas less aggressive tumors such as ER+ breast cancers seem to be more homogeneous, as suggested by Groheux et al [43].…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography/computed tomography (PET/CT) with 18 F fluorodeoxyglucose ([ 18 F]FDG) is gaining importance for the staging of patients with large or locally advanced breast cancer [21]. TNBCs often show high [ 18 F]FDG uptake [22][23][24][25][26][27][28], and several studies have demonstrated correlations between standardized uptake values (SUVs) and histoprognostic factors such as tumor size, grade or Ki67 [24][25][26][27][28][29][30][31][32][33][34][35]. Some studies have analyzed PET parameters' prognostic impact in nonmetastatic breast cancers, with two meta-analyses [36,37] suggesting that Metabolic Tumor Volume (MTV) and Total Lesion Glycolysis (TLG) are correlated with DFS and OS.…”
Section: Introductionmentioning
confidence: 99%